RIDER STRATEGY: ITS EFFECTIVENESS IN DEVELOPING LISTENING SKILLS - Hellien J Loppies (JURNAL TAHURI, 2019)
This study was conducted to determine the effectiveness of RIDER Strategy to improve students’ listening comprehension in one high school in Ambon-Indonesia. The research design is quasi experimental with pre-post test non-equivalent control group design. This research involved two groups of samples; experimental group and control group. The result shows that there is significance improvement on students’ listening comprehension after implementing RIDER Strategy. The students’ mean score increases to 66.05 from 44.82. RIDER Strategy has been succeeding to improve students’ listening comprehension and motivate students to develop their listening skills